Analysis of the Effect of Liquidity, Inventory Variability on Profit Before Tax for FIFO & Average Inventory Accounting Methods - Maulida, Aufa Fahmadia Jihan; Kurniawan, Elan (Summa : Journal of Accounting and Tax, 2023)
This study aims to determine the effect of liquidity inventory variability on profit before tax for the Fifo and average inventory method. The sample used in this study is a pharmaceutical company listed on the Indonesia Stock Exchange during the research period 2016-2020, which presents reports of financial statements that have been audited successively, with eight companies as research samples using the purposive sampling method. The results of research with discriminant analysis Liquidity have a significant effect on Profit Before Tax for the FIFO Inventory Method, and the average discriminant analysis of Inventory Variability has a substantial effect on Profit Before Tax for the FIFO Inventory Method and the average in the Pharmaceutical sector listed on the Indonesia Stock Exchange for the period 2016 -2020.